Cross Link: An Artificial Intelligence Based Solution for Elderly Healthcare - Henriquez, Diego (2024)
Cross Link is a concept idea of a wearable device specifically designed to notify healthcare issues related to the elderly. Its functionality is powered by neural networks, enabling the detection of heart disease conditions, while the usage of machine learning algorithms is involved in analyzing body position and motion to detect falls. The proposed system design offers a custom notification system that can be adapted to the user’s needs. For the development of the article, several architecture diagrams have been prepared, which are divided into hardware and software diagrams. These diagrams show the operational flow, bracelet architecture, neural network model, user database, and deployment of software components. For the evaluation of the diagrams and the solution proposal, a focus group from laboratory Universidad Peruana de Ciencias Aplicadas experts is carried out, who evaluate the feasibility of the diagrams and share their observations about the project. The approval of the diagrams provides a solid foundation for future developments. The project presents viability and work for getting a prototype for the next months.